(untitled) (Culturas Científicas, 2025)
The predictive power of quantum mechanics is virtually unmatched. However, there is no clarity—let alone consensus—about what the theory tells us about the nature of the world. This grand question has generated passionate debates over time; the problem is that these debates have often been conducted with little rigor or conceptual precision. No‑go theorems in the foundations of quantum mechanics offer a solid theoretical framework for addressing these questions in a more systematic and objective manner. The purpose of this manuscript is to examine a select set of these results, consisting of the EPR argument, Bell’s theorem, the Kochen‑Specker theorem, Maudlin’s trilemma and the PBR theorem. The goal is to provide a framework for exploring conceptual questions in quantum mechanics in a more rigorous and precise manner.